The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Bergey's Manual of Systematics of Archaea and Bacteria 2017
DOI: 10.1002/9781118960608.gbm01393
|View full text |Cite
|
Sign up to set email alerts
|

L utispora

Abstract: Lu.ti.spo'ra. L. n. lutum mud, sludge; Gr. fem. n. spora a seed and, in biology, a spore; N.L. fem. n. Lutispora a spore‐forming organism that lives in anaerobic sludge. Firmicutes / Clostridia / Clostridiales / Gracilibacteraceae / Lutispora Straight or slightly curved rods, about 0.6–0.8 × 5.0–8.5 µm. Gram‐stain negative, but Gram‐positive cell‐wall structure. Weakly motile due to laterally inserted flagell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The major findings of this study are that: (a) there are no significant differences in αor β-diversity between MDD and controls; (b) there is no clear difference in relative abundance of species between MDD and controls; and (c) LEfSe analysis revealed that the Rhodospirillaceae family (Gram-negative, rod-shaped to spirillum-formed, purple non-sulfur bacteria which comprise 34 genera; [36,37]), Hungatella genus (anaerobic, Grampositive bacterial genus from the family of Clostridiaceae; [38]), and the species Clostridium bolteae (anaerobic, Gram-positive, rod-shaped, spore-forming bacteria, [39]), Hungatella hathewayi (anaerobic, Gram-positive bacterium, [40]) and Clostridium propionicum (anaerobic, Gram-positive, rod-shaped bacteria, [41]) were significantly enriched in the MDD group. In contrast, Desulfovibrio piger (aerotolerant, Gram-negative bacteria, [42]), Ruminococcus callidus (anaerobic, Gram-positive bacteria; [47]), Coprococcus comes (anaerobic Gram-positive, cocci, [43]), Gemmiger formicilis (anaerobic weakly Gram-positive bacteria; [65]), Phascolarctobacterium succinatutens (strictly anaerobic, Gram-negative bacteria; [45]), Lutispora (anaerobic, Gram-stain-negative and Gram-positive cell-wand structure; [66]), and Gracillibacteraceae (belonging to the Firmicutes phylum) are enriched in the control group.…”
Section: Key Findings Of Our Studymentioning
confidence: 99%
“…The major findings of this study are that: (a) there are no significant differences in αor β-diversity between MDD and controls; (b) there is no clear difference in relative abundance of species between MDD and controls; and (c) LEfSe analysis revealed that the Rhodospirillaceae family (Gram-negative, rod-shaped to spirillum-formed, purple non-sulfur bacteria which comprise 34 genera; [36,37]), Hungatella genus (anaerobic, Grampositive bacterial genus from the family of Clostridiaceae; [38]), and the species Clostridium bolteae (anaerobic, Gram-positive, rod-shaped, spore-forming bacteria, [39]), Hungatella hathewayi (anaerobic, Gram-positive bacterium, [40]) and Clostridium propionicum (anaerobic, Gram-positive, rod-shaped bacteria, [41]) were significantly enriched in the MDD group. In contrast, Desulfovibrio piger (aerotolerant, Gram-negative bacteria, [42]), Ruminococcus callidus (anaerobic, Gram-positive bacteria; [47]), Coprococcus comes (anaerobic Gram-positive, cocci, [43]), Gemmiger formicilis (anaerobic weakly Gram-positive bacteria; [65]), Phascolarctobacterium succinatutens (strictly anaerobic, Gram-negative bacteria; [45]), Lutispora (anaerobic, Gram-stain-negative and Gram-positive cell-wand structure; [66]), and Gracillibacteraceae (belonging to the Firmicutes phylum) are enriched in the control group.…”
Section: Key Findings Of Our Studymentioning
confidence: 99%
“…The major findings of this study are that a) there are no significant differences in α-or β-diversity between MDD and controls; b) there is no clear difference in relative abundance of species between MDD and controls; and c) LEfSe analysis revealed that the Rhodospirillaceae family (Gram-negative, rod-shaped to spirillium-formed, purple non-sulfur bacteria which comprise 34 genera; [37,38]), Hungatella genus (anaerobic, Gram-postive bacterial genus from the family of Clostridiaceae ; [39]), and the species Clostridium bolteae (anaerobic, Gram-positive, rod-shaped, spore-forming bacteria, [40]), Hungatella hathewayi (anerobic, Gram-postive bacterium, [41]), and Clostridium propionicum (anaerobic, Gram-positive, rod-shaped bacteria, [42]) were significantly enriched in the MDD group. In contrast, Desulfovibrio piger (aerotolerant, Gram-negative bacteria , [43]), Ruminococcus callidus (anaerobic, Gram-positive bacteria; [48]), Coprococcus comes (anaerobic Gram-postive, cocci, [44]), Gemmiger formicilis (anaerobic weakly Gram-postive bacteria; [66]), Phascolarctobacterium succinatutens (strictly anaerobic, Gram-negative bacteria; [46]), Lutispora (anaerobic, Gram-stain-negative and Gram-positive cell-wand structure; [67]) and Gracillibacteraceae (belong to the Furmicutes phylum) are enriched in the control group.…”
Section: Discussionmentioning
confidence: 99%